2020
DOI: 10.1186/s12985-020-01384-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-hepatitis E antibodies and antigens among HIV-infected patients in Fars Province, southern Iran

Abstract: Objective HIV-infected patients have immunological and clinical features that might affect the pathogenesis, as well as the outcome of the HIV/HEV co-infection. The current study aimed to determine the seroprevalence of anti-HEV antibodies and HEV antigens among HIV-infected patients in Fars Province, Southwest Iran. Methods Blood samples (5 mL) were collected from 251 HIV-confirmed patients. Respective data, including patients’ demographic information, were obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…In a noble nding, the study revealed that 6.7% of seropositive and 8.2% of seronegative individuals were aware of hepatitis vaccination although no signi cant association was reported. On the other hand, 0.6% of seronegative and none of the seropositive street sweepers were aware of the treatment of hepatitis with no statistically signi cant association (20). Vaidya and Asaei's studies revealed that the seroprevalence of anti-HEV IgG is directly related to age in sewage collectors, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a noble nding, the study revealed that 6.7% of seropositive and 8.2% of seronegative individuals were aware of hepatitis vaccination although no signi cant association was reported. On the other hand, 0.6% of seronegative and none of the seropositive street sweepers were aware of the treatment of hepatitis with no statistically signi cant association (20). Vaidya and Asaei's studies revealed that the seroprevalence of anti-HEV IgG is directly related to age in sewage collectors, which is in accordance with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The primary idea has suspected a higher rate, more signi cant than the normal population, due to common route of transmission (fecal-oral) and exposure of this particular group to sewage, contaminated water, and poor occupational hygiene, especially when eating and drinking at work. A study carried out by Asaei et al in Shiraz reported the sero-prevalence of 13.4% for total anti-HEV among the healthy population (20). Recently, it has been reported that 10.4% (26/151) of HIV infected patients in Fars Province were positive for anti-HEV Ab (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a lower prevalence than previously reported in the Central African Republic (68%), 18 China (44%), 19 Nepal (43%), 20 Spain (26%), 21 but higher than the one described in Iran (10.4%) 22 and Brazil (6.7%) 23 . In Denmark, a large series of 2506 patients with HIV was investigated over three decades: The overall HEV seroprevalence rates were stable during the 1980s, 1990s, and 2000–2013 (23.1%, 22.9%, and 23.7%, respectively) 24 .…”
Section: Discussioncontrasting
confidence: 80%
“…Every year, infection with the human immunodeficiency virus (HIV) resulting in acquired immune deficiency syndrome (AIDS) affects around 2 million people worldwide and 40,000 Americans, which leads to lifelong infection, accompanied by several co-infecting diseases in addition to high mortality rates with no effective treatment up to now (430,431). Stem cell therapy using PSCs has the potential to continuously replace T-lymphocytes, along with the inevitable occurrence of the graft versus host effect which can subsequently eliminate the reservoir from the old-infected cells and substitute them with healthy, new cells (432)(433)(434)(435)(436).…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%